Liquid‐Crystal High‐Frequency Microwave Technology: Materials and Characterization. Issue 2 (13th December 2018) - Zografopoulos, Dimitrios C.; Ferraro, Antonio; Beccherelli, Romeo
Abstract: Ever since the advent of microwave technology, tunable devices, such as phase shifters, resonators, and antennas, have been indispensable in applications requiring radiofrequency signal filtering, beam shaping, or steering. This necessity becomes even more relevant in view of a new era in high‐bandwidth wireless communications in 5G networks, satellite links, and advanced radars for sensing and safety. As the operating frequency is pushed toward the millimeter‐wave range or beyond, the performance of traditional microwave tunable elements, such as PIN diodes, micro‐electromechanical system switches, ferrites, or ferroelectric films, degrades, while their fabrication complexity and cost increases. In this respect, liquid crystals present a promising solution, as they provide continuous tuning, low dielectric constants, moderate losses, low dispersion, and potentially low cost. Here, a comprehensive overview of the available microwave liquid crystal materials is provided, including their key application‐relevant properties, and the techniques employed for their characterization, focusing on the spectrum above 1 GHz. Their performance metrics in terms of dielectric constant tunability, response speed, insertion losses are discussed and guidelines for their selection in different microwave applications are provided. Moreover, the differences observed in the experimental data regarding their characterization are highlighted and possible sources of the observed discrepancies are discussed. Abstract : Liquid crystals, a special class of anisotropic, electro‐optically controlled materials, are rapidly infiltrating the microwave technology, boosting components, and systems with advanced functionalities. The state‐of‐the‐art on the synthesis and characterization of liquid crystals for microwave applications is reviewed, highlighting both the technological challenges and the advantages of using these smart tunable materials.